Translating policy: governmentality and the reflective teacher. Issue 6 (2nd November 2017) - Perryman, Jane; Ball, Stephen J.; Braun, Annette; Maguire, Meg
Abstract: This paper deploys some concepts from the work of Michel Foucault to problematise the mundane and quotidian practices of policy translation as these occur in the everyday of schools. In doing that, we suggest that these practices are complicit in the formation of and constitution of teacher subjects, and their subjection to the morality of policy and of educational reform. These practices are some ways in which teachers work on themselves and others, and make themselves subjects of policy. We conceive of the processes of translation, its practices and techniques as a form of ethics, the constitution of a contemporary and contingent version of professionalism through the arts of self-conduct. In all of this, it is virtually impossible to separate out, as Foucault points out, capability from control. We argue that the development of new capacities, new skills of classroom management, of pedagogy, bring along with it the intensification of a power relation. We are primarily concerned with Foucault's third face of power, pastoral power or government and how this interweaves and overlap with other forms of power within processes of policy and educational reform.